Effect of Three Types of Planting Media and Nutrition on the Growth and Yield of Lettuce (Lactuca sativa L.) - Wandana, Alit; Amalia, Lia; Taryana, Yana (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2021)
The experiment was conducted for three months, from August to October 2019. At the horticultural greenhouse of the Center for Supervision and Certification of Food and Horticultural Plant Seeds (BPSBTPH) in the province of West Java. The purpose of the experiment is research to study the interaction effect of three types of growing media and nutrients on growth and yield of lettuce plants. This research is descriptive and verified by an experimental approach in the horticultural greenhouse of the Center for Supervision and Certification of Food and Horticultural Plant Seeds (BPSBTPH) in the province of West Java. The experimental design used is the "strip plot" method. The results of the experiment showed that treatment of planting media (M) had a significant effect on leaf number, root volume, plant sap weight, and root / pupil ratio. Nutrition (N) treatment significantly affected leaf area index parameters, number of leaves, root volume, fresh fruit weight of the plant, and root drop rate. The interaction between the planting medium and the nutrient intakes had a very significant effect on the number of leaves, the volume of the roots, the weight of the sap and the rate of root loss